2013
DOI: 10.1002/pits.21742
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Class Pass Intervention for Typically Developing Students With Hypothesized Escape‐motivated Disruptive Classroom Behavior

Abstract: The aim of this study was to evaluate the Class Pass Intervention (CPI) as a secondary intervention for typically developing students with escape-motivated disruptive classroom behavior. The CPI consists of providing students with passes that they can use to appropriately request a break from an academic task to engage in a preferred activity for preset amount of time. In addition, students are incentivized to not use the class passes by continuing to engage in the academic task and instead exchanging them for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…In reviewing the 121 articles to down-select the final articles for in-depth analyses, we excluded the following studies because there was no evidence in their method section to indicate that the target students received universal Tier 1 supports within SWPBIS before receiving the Tier 2 intervention, or that the school was implementing a universal Tier 1 support for all students: two studies on CICO (Collins, Gresham, et al, 2016;March & Horner, 2002), a study on the Class Pass Intervention (CPI; Cook et al, 2014), a study on the Mystery Motivator (Beeks & Graves, 2016;Kraemer et al, 2012), and a study on self-monitoring (Clemons et al, 2016). To ensure coding consistency and reliability, interrater agreement was assessed, as calculated by dividing agreements between raters by agreements plus disagreements and multiplying by 100.…”
Section: Article Selection Criteriamentioning
confidence: 99%
“…In reviewing the 121 articles to down-select the final articles for in-depth analyses, we excluded the following studies because there was no evidence in their method section to indicate that the target students received universal Tier 1 supports within SWPBIS before receiving the Tier 2 intervention, or that the school was implementing a universal Tier 1 support for all students: two studies on CICO (Collins, Gresham, et al, 2016;March & Horner, 2002), a study on the Class Pass Intervention (CPI; Cook et al, 2014), a study on the Mystery Motivator (Beeks & Graves, 2016;Kraemer et al, 2012), and a study on self-monitoring (Clemons et al, 2016). To ensure coding consistency and reliability, interrater agreement was assessed, as calculated by dividing agreements between raters by agreements plus disagreements and multiplying by 100.…”
Section: Article Selection Criteriamentioning
confidence: 99%
“…As discussed previously, the CPI was designed as a targeted, Tier 2 intervention for students with off‐task, disruptive classroom behavior. Specifically, the CPI was designed purposefully to include both negative and positive reinforcement components to be useful as a targeted intervention for students with a variety of functions maintaining their off‐task, disruptive behavior (see Cook et al., , for greater explanation of the intervention). Each student was explicitly trained in one 30‐min session by the teachers, with the assistance of a graduate research assistant.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study indicated that the CPI was effective at reducing hypothesized escape‐motivated behavior in three typically developing elementary‐age children (Cook et al., ). These three students were selected for the study using a modified multiple‐gating technique.…”
Section: The Class Pass Interventionmentioning
confidence: 97%
See 1 more Smart Citation
“…Collins et al (2016) suggested that it might be beneficial to consider individual differences in academic skills as individuals with lower academic skills may need a supplementary intervention to address the difficulty of tasks from which escape is highly reinforcing. Although the CPI was originally designed for addressing escape-motivated disruptive behavior, Cook et al (2014) and Collins et al (2016) suggested that the CPI could address multiple functions of disruptive behavior, making it an option for a larger target population. The CPI can address multiple functions by providing negative reinforcement in the form of escape from a task or positive reinforcement if the break includes access to (a) a tangible or activity, (b) attention, or (c) sensory stimulation.…”
mentioning
confidence: 99%